ANALISIS PENGARUH LEVERAGE, CORPORATE GOVERNANCE, DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023 - Nabila, Devita Mia Divia; Suprianto, Didik Tugas; Handayani, Alberta Esti (Politeknik Negeri Ambon, 2025)
Introduction: Tax avoidance is an essential issue in taxation that often exploits regulatory gaps or legal ambiguities in complex transactions. This practice poses a challenge for tax authorities in enforcing compliance. This study examines the influence of leverage, corporate governance, and transfer pricing on tax avoidance in manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange during the period 2021-2023.Methods: The method employed is quantitative, utilising secondary data from a total sample of 35 companies over three years, resulting in a total of 65 data observations. The analysis methods employed in this research include descriptive statistics, classical assumption tests (such as normality, multicollinearity, heteroscedasticity, and autocorrelation), and hypothesis testing. Additionally, t-tests, F-tests, and multiple linear regression analyses are conducted, along with the coefficient of determination, using SPSS version 25.Results: Leverage and transfer pricing have a significant impact on tax avoidance, whereas corporate governance does not. All three variables — leverage, corporate governance, and transfer pricing —have a substantial effect on tax avoidance. Keywords: Leverage, Corporate Governance, Transfer Pricing, Tax Avoidance